INCIDENCE OF ISOPARORCHlS HYPSELOBAGRI (BILLET, 1898) (fREMATODA, HEMIURIDAE) AMONG THE CATFISHES OF BHAVANISAGAR RESERVOIR - Devaraj, M; Ranganathan, V (Indian Journal of Fisheries, 2011)
Southwell (1913) described lsoparorchis hypselobagri. found inside the cavityof the air-bladdel of a freshwater catfish, WaJlago attu, caught from a tank atBankipur, Bengal. He observed cent per cent infection in the adult W, attu examined.According to him, the worms collected by Capt. Parker in 1910 from the flesh of themabseer, Barhus tor, were immature I. hypselobagri. Achan (1956) recorded 65per cent infection among this fish in the Bhavanisagar reservoir with a maximum offOfty worms in a single host.The incidence of this worm in the air-bladder of W. atfu, in the viscera andbody musculature of Ca/lichrous bimaculatus and the destruction of the ovary inMystus oar and some aspects of host-parasite relationship based on observationsmade during 1964-65 are described in this communication.